The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1021/acsnano.9b05049
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Tunneling in a Hybrid of Single-Walled Carbon Nanotubes and Graphene

Abstract: Transparent and conductive films (TCFs) are of great technological importance.The high transmittance, electrical conductivity and mechanical strength make singlewalled carbon nanotubes (SWCNTs) a good candidate for their raw material. Despite the ballistic transport in individual SWCNTs, however, the electrical conductivity of their networks is limited by low efficiency of charge tunneling between the tube elements. Here, we demonstrate that the nanotube network sheet resistance at high optical transmittance i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 50 publications
1
18
0
Order By: Relevance
“…189 Even though carbon nanotubes are generally acknowledged for their high conductivity, their resistance can further be decreased by more than 50% if they form hybrids with graphene, due to enhanced effectiveness of charge tunneling. 190 Lately, such a hybrid electrocatalyst based on graphene nano-akes (GFs) and carbon nanotubes (CNTs) doped with heteroatoms such as N, Co and Mo (N-Co-Mo-GF/CNT) was studied for its ORR and OER activity by Tavakkoli et al 51 The OER catalytic activity was investigated by means of SECM in SG/TC mode in alkaline media on two different substrates, namely nickel (Ni) and glassy carbon (GC). When GC was used, the tip response (increase of ORR current) was almost simultaneous with the oxygen generation (OER onset potential), compared to the Ni substrate in which case the tip response was delayed (Fig.…”
Section: Bifunctional Electrocatalysts For the Orr And Oermentioning
confidence: 99%
“…189 Even though carbon nanotubes are generally acknowledged for their high conductivity, their resistance can further be decreased by more than 50% if they form hybrids with graphene, due to enhanced effectiveness of charge tunneling. 190 Lately, such a hybrid electrocatalyst based on graphene nano-akes (GFs) and carbon nanotubes (CNTs) doped with heteroatoms such as N, Co and Mo (N-Co-Mo-GF/CNT) was studied for its ORR and OER activity by Tavakkoli et al 51 The OER catalytic activity was investigated by means of SECM in SG/TC mode in alkaline media on two different substrates, namely nickel (Ni) and glassy carbon (GC). When GC was used, the tip response (increase of ORR current) was almost simultaneous with the oxygen generation (OER onset potential), compared to the Ni substrate in which case the tip response was delayed (Fig.…”
Section: Bifunctional Electrocatalysts For the Orr And Oermentioning
confidence: 99%
“…the y-direction) to avoid any interaction with spurious replica images. Out of the wide range of available chiralities, CNT (5,5), (6,6), (7,7), (8,8), (9,9), (10,10) and (11,11) for forming the systems of armchair SWNT-SLG and CNT(8,0), CNT(10,0), CNT(13,0) and CNT(16,0) for making the systems of zigzag SWNT-SLG were chosen.…”
Section: Structural Detailsmentioning
confidence: 99%
“…Nano-sized carbon allotropes, specially single-walled carbon nanotubes (SWNTs) and single-layer graphene (SLG), are the most widely studied materials due to their extraordinary mechanical, chemical and optical properties [1][2][3][4][5][6] and their exceptional electronic transport makes them a suitable substitute for active layers in future nanoelectronic devices. [7][8][9][10] Devices based on the hybrid system, combining SWNTs and SLG, have shown great potential in terms of electrical conductivity 11 and mechanical strength, 12 and also have found applications in various elds, such as transparent conducting electrodes, 13,14 active layers in TFTs, 15 humidity and gas sensors, 16 biomedical applications, 17 next generation aromatic compound adsorbents, 18 etc. To improve and tune the desired properties for advanced applications such as transparent electrodes and active layers in TFTs, it is very important to understand the structure of SWNT-SLG junction at the atomic scale and various interactions between the two, which modify the properties of the hybrid nanostructures.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the results of DFT calculations performed for an atomistic model comprising one armchair and two zigzag semiconducting nanotubes, it was shown that the addition of graphene flakes introduced additional electronic states at the Fermi level, which increased the current and conductivity of graphene/SWCNT hybrid system [ 30 ]. In turn, it was experimentally revealed that when a SWCNT film is deposited on a graphene substrate, its conductivity increases by approximately the same amount as in chemical doping due to a decrease in the height of the tunnel barrier inside the carbon material [ 31 ]. At the same time, the issues of controlling the conductive properties of graphene/SWCNT hybrid structures by choosing a certain topology of nanotubes and graphene, as well as their mutual orientation in the hybrid architecture, remain poorly understood.…”
Section: Introductionmentioning
confidence: 99%